Aeta Magbukún of Mariveles: Traditional Indigenous Forest Resource Use Practices and the Sustainable Economic Development Challenge in Remote Philippine Regions - Balilla, V.; Anwar McHenry, Julia; McHenry, M.; Parkinson, R.; Banal, D. (Taylor & Francis, 2012)
The Aeta Magbukún of Mariveles are one of the least known and researched Indigenous peoples remaining on the fringe of the bay, and within the remaining forests in Bataan province on Luzon Island in the Philippines. This work describes the unique cultural systems and language of the Aeta Magbukún tribe in Biaan, Mariveles, and both the traditional forest resource use and the evolving new subsistence practices developed to adapt to the encroachment of non-Indigenous peoples onto ancestral lands. The Aeta's forest resource use practices are discussed from a sustainable Indigenous development context within unique socioeconomic, cultural, and environmental circumstances in Bataan.